Human T-lymphotropic virus 1/2 infection among prisoners of a major penitentiary complex of Goiás State, Central-West Brazil - Okita, Michele Tiemi; de Matos, Marcos André; Freitas, Nara Rúbia de; Silva, Ágabo Macedo da Costa e; Marques, Juliana Menara de Souza; Marinho, Thaís Augusto; Matos, Márcia Alves Dias de; Martins, Regina Maria Bringel (Frontiers in Public Health, 2024)
Introduction Studies on human T-lymphotropic virus 1/2 (HTLV-1/2) infection are scarce in incarcerated population. Therefore, this study estimated the prevalence of HTLV-1/2 infection among prisoners of the major penitentiary complex of Goiás State, Central-West Brazil, comparing it with available data from other Brazilian regions. Methods A cross-sectional study was conducted with 910 prisoners of the major penitentiary complex in the State of Goiás, Central-West Brazil. All participants were interviewed, and their serum samples were tested for anti-HTLV-1/2 using an enzyme-linked immunosorbent assay (ELISA; Murex HTLV-I + II, DiaSorin, Dartford, UK). Seropositive samples were submitted for confirmation by a line immunoassay (INNO-LIA HTLV I/II, Fujirebio, Europe N.V., Belgium). Results The majority of participants were males (83.1%), between 25 and 39 years old (56.1%; mean age: 31.98 years), self-reported brown ethnicity (56.2%) and reported 9 years or less of formal education (41.4%). Most reported using non-injectable illicit drugs and various sexual behaviors that present risk for sexually transmitted infections (STIs). The prevalence of anti-HTLV-1/2 was 0.33% (95% CI: 0.07–0.96), HTLV-1 (0.22%) and HTLV-2 (0.11%). The two HTLV-1 seropositive prisoners reported high-risk sexual behaviors, and the HTLV-2 seropositive individual was breastfed during childhood (> 6 months) by her mother and three other women. Conclusion These data revealed a relatively low seroprevalence of HTLV-1/2 in prisoners in Central-West Brazil, and evidence of HTLV-1 and HTLV-2 circulation in the major penitentiary complex of Goiás State. Given the prevalence of high-risk sexual behaviors, there is a crucial need to intensify education and health programs in prisons to effectively control and prevent HTLV-1/2 and other STIs.